La Biennale di Venezia : the experience of art. - Biennale Venetië 2005; Ahtila, Eija-Liisa; Aliaga, Juan Vicente; Barak, Ami; Blum, Andrea; Boutoux, Thomas; Bruguera, Tania; Buchloh, Benjamin H.D.; Cameron, Dan; Carlos, Isabel; Chessa, Silvia; Chieh-Jen, Chen; et al. (Venezia : La Biennale di Venezia, 2005)
Ahtila, Eija-Liisa ; Araujo, Vasco ; Bacon, Francis ; Balka, Miroslaw ; Blum, Andrea ; Bonvicini, Monica ; Breitz, Candice ; Bruguera, Tania ; Chiehjen, Chen ; Damasceno, José ; Dean, Tacita ; Doherty, Willie ; Douglas, Stan ; Dumas, Marlene ; Erlich, Leandro ; Frize, Bernard ; Graham, Dan ; Guston, Philip ; Hernandez Pijuan, Juan ; Holzer, Jenny ; Kentridge, William ; Kruger, Barbara ; López, Maider ; Louro, Joao ; Macchi, Jorge ; Martin, Agnes ; Meireles, Cildo ; Mtethwa, Zwelethu ; Muñoz, Juan ; Nauman, Bruce ; Orozco, Gabriel ; Perejaume ; Rhode, Robin ; Ruff, Thomas ; Schütte, Thomas ; Tàpies, Antoni ; Uslé, Juan ; Vezzoli, Francesco ; Wallinger, Mark ; Weischer, Matthias ; Whiteread, Rachel ; Yang, Jun
Biennale di Venezia, Venetië, 2005-06-12 tot 2005-11-06
boek